Linear sound attenuation model for assessing external stimuli in prenatal period. (1st September 2018) - Bieńkowska, Maria; Mitas, Andrzej W.
Abstract: The popularization of acoustic stimulation during the prenatal period encourages the analysis of sounds reaching the inside of the uterus. To assess the distortion of any sound stimuli, a mathematical model of attenuation has to be used. In this paper a mathematical model is proposed on the basis of data from a physical model. The physical model consisted of muscle slices of two different thicknesses placed in a tank filled with water. The amplitudes of sinusoidal waves between 160 and 2000 Hz were measured under the water surface. Using the collected data, a linear mathematical model of sound attenuation on the way to the fetal ear was created. The results indicated a rise in the amount of sound attenuation for increasing frequencies. Analysis of slope coefficients for two muscle thicknesses revealed that there is no significant difference between attenuation by the thinner and the thicker tissue. Finally, the model was verified with data obtained during experiments on animals. The proposed model of the sound transmission allowed assessment of the attenuation by a soft tissue. It reveals changes in the sound reaching fetal ears, which can make acoustic stimulation different than what is heard in postnatal life. The model can be used to simulate the distortion of any sound which is proposed to prenatal stimulation and to assess its quality.